Digital Reconstruction of Ethnopedagogy : Integration of Local Historical Narratives of North Sumatra into the Merdeka Curriculum in the PGSD Study Program - Karina Wanda; Anik Ghufron; Ibnu Syamsi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The rapid advancement of digital technology has transformed educational practices while simultaneously posing challenges to the preservation of local cultural values. This study aims to develop and evaluate a digital ethnopedagogical reconstruction model that integrates local historical narratives of North Sumatra into the Merdeka Curriculum within the Primary School Teacher Education (PGSD) program. Employing a Research and Development (R&D) approach with the 4D model, this study utilized a mixed-methods design involving document analysis, interviews, observations, expert validation, and field trials. The findings reveal that local historical narratives—comprising folkloric legends, educational acculturation, and the heritage of local sultanates—possess strong ethnopedagogical potential when reconstructed through interactive digital media. Quantitative results demonstrate a significant 38% increase in students’ ethnopedagogical understanding, supported by high content validity (89%) and media feasibility (92%) scores. Qualitative findings further indicate enhanced cultural awareness, historical empathy, and learner engagement. The study concludes that the effectiveness of digital ethnopedagogical innovation is primarily determined by its pedagogical integration within the learner-centered framework of the Merdeka Curriculum. This research contributes a sustainable model for culturally grounded digital pedagogy in teacher education.